SERIOUS GAME FOR THE READING SKILLS OF CHILDREN AT AN EARLY AGE - Previa Yanti, Putri
One of the focuses of the Government of Indonesia to generate quality human resources is illiteracy eradication. Based on the survey by the Statistics Indonesia in 2018, 3.29 million people in the country were illiterate. The number can be reduced by honing the reading skills of children at an early age. Children’s reading skills start to develop at 2 years until they can read fluently at 7 years. The development is followed by, and well-coordinated with, their rapid physical growth, readying them to learn to develop their abilities. Using serious game to hone children’s reading skills can increase the outcome of their reading learning activities at an early age. The entertainment and the learning elements in serious game were balanced using procedural content generation. In addition, to provide various challenge, the game was also designed to have several levels of difficulty. The levels were arranged in accordance with a teaching matrix for reading skills to help the players learn to read. The game was tested two times against children of 6–8 years. Their reactions to the game indicated that it was adequately acceptable against the testing variables, i.e. learning, engagement, immersion, challenge, skill, concentration, coal clarity, feedback, and autonomy, with the average score of >4. From the two tests, the average learning outcomes increased from 84.29 to 91.23. The N-Gain value was 0.44 (medium category), indicating that learning to read using the game adequately improved the learning effectivity in children.